Pengaruh Penambahan Zat Aditif Terhadap Penurunan Emisi Gas Buang Pada Sepeda Motor Suzuki Satria 150 FU Tahun 2010 Dengan Bahan Bakar Pertalite - Priyanto, Teguh; Budiyono, Budiyono; Prasetyo, Imam (Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
This research was conducted to determine the effect of adding additives to reducing exhaust emissions on a Suzuki Satria 150 FU Motorcycle in 2010 with fuel. This research used a Suzuki Satria 150 FU motorcycle in 2010. The research method used in this study is the method experiment by using tables and graphs to process the data, By using the Gas Analyzer emission test tool to measure exhaust gas emissions of HC, and CO. The results of the research mixing pertalite fuel with the addition of salvis fuel additive and Eco Racing, pertalite fuel using salvis fuel additive in the amount of 1 ml per liter and 1 Eco Racing per liter at engine speed 1. Testing at idle 1500 rpm, 2000 rpm, 2500 rpm, 3000rpm, 3500rpm, 4000rpm Keywords: Exhaust Emissions, Pertalite, Additives, CO,Keywords: Exhaust Emissions, Pertalite, Additives, CO,